Sintesis Pupuk Ca(No3)2 dari Limbah Industri Bleaching Earth - Luh Eka Meidiani Pujahashita; Dirga Tirta Sampelawang; Dwi Hery Astuti; Sani Sani; Srie Mulyani (Publikasi Indonesia, 2022)
Bleaching earth industrial waste is usually disposed of and landfilled in solid waste disposal. This waste is rich in calcium and sulfur content so that it has the potential as a raw material for making Calcium Nitrate fertilizer. This research aims to process bleaching earth industrial waste into calcium nitrate fertilizer which is rich in the macronutrient Nitrogen and the micronutrient Calcium in accordance with EU Agricultural standards. This research method was carried out by reacting the waste with nitric acid at different concentrations, 0.8M; 1M; 1.2M; 1.M; and 1.6M while being heated at different temperatures, at 50℃, 55℃, 60℃, 65℃, and 70℃, using a magnetic stirrer with a stirring speed of 350 rpm. Then filtered to remove impurities with the filtrate. The filtrate is added with ammonium hydroxide, so that a solid is formed and the pH has reached a neutral atmosphere, then it is filtered and left to stand at room temperature. XRF analysis was carried out to add elements contained in the fertilizer and Kjedahl Spectrophotometer to indicate the total N-content. The highest yield was obtained at a concentration of 1.6 M with a yield of 95.4440% with an actual weight of 2.3861 grams with an operating temperature of 70oC and for the best Calcium content, it was obtained at 23.3% with a N-Total content of 0.64% which complies with the EU Agriculture Commission Standard.